Gastrointestinal stromal tumors regulate macrophage M2 polarization through the MIF/CXCR4 axis to immune escape - Xiao, Shuo-meng; Xu, Rui; Yang, Ying-xin; Zhao, Rui; Xie, Yuan; Lei, Xu-dan; Wu, Xiao-ting (Frontiers in Immunology, 2024)
The infiltration of immune cells and their roles of the infiltrating-immune cells in gastrointestinal stromal tumor (GIST) is still unclear. We aimed to discover the infiltration cell types and the relationship between the infiltrating-immune cells and the progression of GIST. Experimental design: Single-cell RNA sequencing were performed to discover types of the infiltrating-immune cells and to analyze CellChat between cells. Immunohistochemistry of 80 GIST samples were used to clarify the relation between macrophages and recurrence risk. In vitro, flow cytometry and Real-time PCR were performed to uncover a potential mechanism of tumor cell regulation of macrophages.Results: Tumor cells, macrophages, and T-cells were the predominant cell types. The MIF/CXCR4 axis was the most common ligand-receptor interaction between macrophages and tumor cells. As the risk increased, expression levels of CD68, CD206, MIF, and CXCR4 gradually increased. In vitro, we found that GIST882 was able to secrete MIF and GIST882 cell supernatant upregulated M2 polarization. Real-time PCR showed that expression levels of IL-10 mRNA and Arginase-1 mRNA were also the highest in the GIST882 cell supernatant group.Conclusions: These findings identify that macrophages are the most abundant infiltrating cells in GIST. The MIF/CXCR4 axis is the most common ligand-receptor interaction between macrophages and tumor cells. GIST cells can regulate macrophage M2 polarization through the MIF/CXCR4 axis.